2020
DOI: 10.35378/gujs.677970
|View full text |Cite
|
Sign up to set email alerts
|

Mericarp and Seed Morphology of the genus Althaea L. (Malvaceae) in Turkey

Abstract: Seed morphology of four Lavatera species distributed in Turkey were investigated via light microscope (LM) and scanning electron microscope (SEM) to determine their seed macro-and micromorphological characters and to assess the diagnostic value of these features. The seeds are dark brown in color and reniform with rounded apex and base reniform in shape. The dimension of seeds ranges between 1.68-2.89 mm in length and 1.51-2.4 mm in width. Also seeds are glabrous, strophiolate and hilum at basal. Two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…They were investigated and photographed with SEM (JEOL JSM 6060 LV, Tokyo, Japan) at a voltage of 15 kV in the Prof. Dr. Zekiye Suludere Electron Microscopy Laboratory at the Gazi University, Faculty of Science. Terminology was adopted from Barthlott (1981), Abid et al (2016), Özbek & Uzunhisarcıklı, 2020a; 2020b, and Abdel Khalik et al (2021).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were investigated and photographed with SEM (JEOL JSM 6060 LV, Tokyo, Japan) at a voltage of 15 kV in the Prof. Dr. Zekiye Suludere Electron Microscopy Laboratory at the Gazi University, Faculty of Science. Terminology was adopted from Barthlott (1981), Abid et al (2016), Özbek & Uzunhisarcıklı, 2020a; 2020b, and Abdel Khalik et al (2021).…”
Section: Methodsmentioning
confidence: 99%
“…The significance of seed morphological characteristics in plant systematics for the family Malvaceae has been emphasized in some studies (Ahmed & Qaiser, 1989; Ather et al, 2009; Kirkbride et al, 2006; Masullo et al, 2020; Özbek & Uzunhisarcıklı, 2020a; 2020b; Sivarajan & Pradeep, 1996). Paul and Nayar (1987) examined the seeds of 54 taxa under 17 genera using SEM, and said that the variation in the seed coat surface differs from species to species, even in infraspecific ranks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of 17, light beige to chocolate brown very large seed, while B. australis is dusty black. Özbek & Uzunhisarcikl (2020) demonstrated that dimension and seed pattern is important morphological characters for the separation of the studied taxa.…”
mentioning
confidence: 89%
“…The most useful features for seed recognition include the seed shape, colour, hilum shape, ornamentation, and seed weight (Ilakiya & Ramamoorthy, 2020;Karakish et al, 2020). Moreover, seed surface patterns have been used to solve taxonomic problems (Karaismailoğlu, 2015(Karaismailoğlu, , 2019Fawzi, 2018;Özbek & Uzunhisarcikl, 2020).…”
Section: Introductionmentioning
confidence: 99%